2013
DOI: 10.1016/j.celrep.2013.09.044
|View full text |Cite
|
Sign up to set email alerts
|

Single-Cell Profiling of Epigenetic Modifiers Identifies PRDM14 as an Inducer of Cell Fate in the Mammalian Embryo

Abstract: Cell plasticity or potency is necessary for the formation of multiple cell types. The mechanisms underlying this plasticity are largely unknown. Preimplantation mouse embryos undergo drastic changes in cellular potency, starting with the totipotent zygote through to the formation of the pluripotent inner cell mass (ICM) and differentiated trophectoderm in the blastocyst. Here, we set out to identify and functionally characterize chromatin modifiers that define the transitions of potency and cell fate in the mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
134
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(146 citation statements)
references
References 44 publications
9
134
3
Order By: Relevance
“…Although it has previously been thought that cells are homogenous until generation of inside and outside cells, more recent studies have opened a new possibility that cells at the 4-cell stage can already exhibit differences in cell fate Tabansky et al, 2013) and developmental potential (Morris et al, 2012;. This led to the suggestion that the differential activity of epigenetic regulators such as CARM1 (Torres-Padilla et al, 2007) or PRDM14 (Burton et al, 2013), or the differential behavior of transcription factors such as Oct4 (Plachta et al, 2011), at the 4-cell stage could be linked to differential cell fate and potential. Here, we sought to address this by first investigating and directly comparing global differences in gene expression between individual cells within the embryo during the first days of development.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although it has previously been thought that cells are homogenous until generation of inside and outside cells, more recent studies have opened a new possibility that cells at the 4-cell stage can already exhibit differences in cell fate Tabansky et al, 2013) and developmental potential (Morris et al, 2012;. This led to the suggestion that the differential activity of epigenetic regulators such as CARM1 (Torres-Padilla et al, 2007) or PRDM14 (Burton et al, 2013), or the differential behavior of transcription factors such as Oct4 (Plachta et al, 2011), at the 4-cell stage could be linked to differential cell fate and potential. Here, we sought to address this by first investigating and directly comparing global differences in gene expression between individual cells within the embryo during the first days of development.…”
Section: Discussionmentioning
confidence: 99%
“…Historically, cells of the early mouse embryo were considered identical in their ability to give rise to embryonic or extra-embryonic lineages, due to the regulative ability of the embryo to compensate for alterations in cell arrangement (Hillman et al, 1972;Tarkowski, 1959). However, more recent evidence has suggested that cells as early as the 4-cell stage become heterogeneous, exhibiting differences in developmental fate and potential (Bischoff et al, 2008;Tabansky et al, 2013) and in the activity of specific cell-fate regulators (Burton et al, 2013;Plachta et al, 2011;Torres-Padilla et al, 2007). This heterogeneity indicates the possibility that the breaking of embryo symmetry starts earlier than expected, prior to differences in cell position and polarity evident from the 16-cell-stage onward (Fleming, 1987;Johnson and Ziomek, 1981).…”
Section: Introductionmentioning
confidence: 99%
“…However, such approaches can examine the expression of only a small number of genes in each experiment, thus restricting our ability to examine co-expression patterns and to robustly identify subpopulations of cells. Protocols have been developed to overcome these limitations by amplifying small quantities of mRNA 4,5 , which, in combination with microfluidics approaches for isolating individual cells 6,7 , have been used to analyze the co-expression of tens to hundreds of genes in single cells 8,9 . These protocols also allow the entire transcriptome of large numbers of single cells to be assayed in an unbiased way.…”
Section: A N a Ly S I Smentioning
confidence: 99%
“…During early embryonic cleavage stages, many chromatin modifiers, co-activators and repressors are expressed in discrete and highly dynamic expression patterns [60]. At the 8-cell stage a unique set of these regulators are expressed, including the demethylases Kdm5a, Kdm6a and Dnmt3l, and these factors are also expressed in later trophoblast cells.…”
Section: Chromatin States and Totipotencymentioning
confidence: 99%